Conversations in Cochlear Implantation: The Inner Ear Therapy of Today - Grant Rauterkus; Anne K. Maxwell; Jacob B. Kahane; Jennifer J. Lentz; Moises A. Arriaga (Biomolecules, 2022)
As biomolecular approaches for hearing restoration in profound sensorineural hearing loss evolve, they will be applied in conjunction with or instead of cochlear implants. An understanding of the current state-of-the-art of this technology, including its advantages, disadvantages, and its potential for delivering and interacting with biomolecular hearing restoration approaches, is helpful for designing modern hearing-restoration strategies. Cochlear implants (CI) have evolved over the last four decades to restore hearing more effectively, in more people, with diverse indications. This evolution has been driven by advances in technology, surgery, and healthcare delivery. Here, we offer a practical treatise on the state of cochlear implantation directed towards developing the next generation of inner ear therapeutics. We aim to capture and distill conversations ongoing in CI research, development, and clinical management. In this review, we discuss successes and physiological constraints of hearing with an implant, common surgical approaches and electrode arrays, new indications and outcome measures for implantation, and barriers to CI utilization. Additionally, we compare cochlear implantation with biomolecular and pharmacological approaches, consider strategies to combine these approaches, and identify unmet medical needs with cochlear implants. The strengths and weaknesses of modern implantation highlighted here can mark opportunities for continued progress or improvement in the design and delivery of the next generation of inner ear therapeutics.